2009
DOI: 10.1111/j.1365-2958.2009.06698.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of staphyloferrin A biosynthetic and transport mutants in Staphylococcus aureus

Abstract: SummaryIron is critical for virtually all forms of life. The production of high-affinity iron chelators, siderophores, and the subsequent uptake of iron-siderophore complexes are a common strategy employed by microorganisms to acquire iron. Staphylococcus aureus produces siderophores but genetic information underlying their synthesis and transport is limited. Previous work implicated the sbn operon in siderophore synthesis and the sirABC operon in uptake. Here we characterize a second siderophore biosynthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
211
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(218 citation statements)
references
References 82 publications
7
211
0
Order By: Relevance
“…Catecholamine hormones have previously been shown to form 2:1 and 3:1 complexes with iron(III) (30). Bacteria equipped with catechol siderophore uptake systems could feasibly import Fe(III)-catecholamine 3 complexes as "pseudosiderophores" for growth under iron-restricted conditions, as recently demonstrated for Bacillus subtilis and Escherichia coli (40).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Catecholamine hormones have previously been shown to form 2:1 and 3:1 complexes with iron(III) (30). Bacteria equipped with catechol siderophore uptake systems could feasibly import Fe(III)-catecholamine 3 complexes as "pseudosiderophores" for growth under iron-restricted conditions, as recently demonstrated for Bacillus subtilis and Escherichia coli (40).…”
mentioning
confidence: 81%
“…The molecular genetics and biochemistry for the synthesis of two S. aureus siderophores, staphyloferrin A (SA) and staphyloferrin B (SB), were recently characterized (7,9). Following capture of extracellular iron, the staphyloferrins are recognized by the highly specific receptors HtsA (SA) and SirA (SB), and at least iron, if not the iron-siderophore complex, is actively imported into the cytosol through permeases (3,7,24,25). Furthermore, it has been shown that genomic inactivation of the staphyloferrin biosynthesis loci sfa (SA) and sbn (SB) eliminates siderophore output and severely curtails S. aureus growth in animal serum (3), prompting the question of whether the target of staphylococcal siderophores in serum is transferrin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chelation occurs through oxygen coordination with characteristic subunits (e.g., trihydroxamate; Figure 1). In addition to common cellular processes that require iron as a cofactor (e.g., TCA cycle, DNA replication), siderophoremediated iron acquisition aids in the virulence of organisms such as Staphylococcus aureus and Pseudomonas aeruginosa [3,4]. To date, >500 siderophores have been discovered and despite their similar function, the structures vary widely, playing a major role in recognition by membrane-bound proteins and diffusion away from cellular membranes [5,6].…”
mentioning
confidence: 99%
“…Consequently, S. aureus has evolved multiple strategies for iron acquisition (7). S. aureus produces two siderophores, staphyloferrin A (8,9) and staphyloferrin B (10), and has a transport system that can co-opt hydroxamate-type siderophores produced by other bacteria (11). S. aureus can also obtain heme from host heme-containing proteins hemoglobin and haptoglobin, transport it across the bacterial cell envelope, cleave the porphyrin ring, and release iron for use by the cell with the well characterized ironregulated surface determinant (Isd) 3 system (12).…”
mentioning
confidence: 99%